2022
DOI: 10.1007/s11739-022-03097-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypernatremia at presentation to the emergency department: a case series

Abstract: Disorders of serum sodium are common findings in patients presenting to the emergency department (ED). The aim of this study was to systematically investigate the prevalence, symptoms, etiology, treatment as well as the course of hypernatremia present on admission to the ED. All adult patients with measurements of serum sodium presenting to the ED between 01 January 2017 and 31 December 2020 were included in this retrospective cohort study. Chart reviews were performed for all patients with hypernatremia defin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Partisipan ternyata diketahui juga memiliki hipersensitivitas terhadap celery sebab 15 menit setelah konsumsi 300 ml jus celery, partisipan menunjukkan tanda sesak napas, dada berdebar, takikardia dan merasa lelah. Adanya keluhan ini menjadi kewaspadaan bahwa partisipan dicurigai mengalami hipernatremia (Ravioli et al, 2022).…”
Section: Pembahasan Hipernatremia Yang Disebabkan Konsumsi Celeryunclassified
“…Partisipan ternyata diketahui juga memiliki hipersensitivitas terhadap celery sebab 15 menit setelah konsumsi 300 ml jus celery, partisipan menunjukkan tanda sesak napas, dada berdebar, takikardia dan merasa lelah. Adanya keluhan ini menjadi kewaspadaan bahwa partisipan dicurigai mengalami hipernatremia (Ravioli et al, 2022).…”
Section: Pembahasan Hipernatremia Yang Disebabkan Konsumsi Celeryunclassified
“…Therefore, it is commonly seen in older patients and in those with mental or physical disorders. Risk factors for hypernatremia include diseases that disrupt thermoregulation, increased fluid loss, excessive salt intake, and disorders such as diabetes insipidus [4,5]. Previous studies have reported that dysnatremia is an indicator of mortality and morbidity in critically ill patients [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Delayed recognition and treatment of hypernatraemia is reported to be associated with increased mortality 15,16 . Even when recognised, inadequate correction of hypernatraemia has also been reported 17 . Concerningly, while hypernatraemia is present in approximately 0.2% of patients on presentation to hospital, it has been documented in up to 1% of hospitalised patients at any point during admission suggesting that a significant proportion of patients develop hypernatraemia while under medical care 13,15,16 …”
Section: Introductionmentioning
confidence: 99%
“…15,16 Even when recognised, inadequate correction of hypernatraemia has also been reported. 17 Concerningly, while hypernatraemia is present in approximately 0.2% of patients on presentation to hospital, it has been documented in up to 1% of hospitalised patients at any point during admission suggesting that a significant proportion of patients develop hypernatraemia while under medical care. 13,15,16 We have defined severe hypernatraemia as a sodium concentration ≥ 155 mmol/L, in line with previously published studies.…”
Section: Introductionmentioning
confidence: 99%